PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM MULTIKULTURAL PADA PESANTREN LANSIA BERORIENTASI BISNIS - Asadori, Asadori; Wahyuni, Sri (TA'LIM : Jurnal Studi Pendidikan Islam, 2024)
This research aims to determine the development of a multicultural Islamic Religious Education curriculum at a business-oriented boarding school for the elderly. The results of this research can be concluded that Islamic education is conscious guidance in developing the potential or abilities of students in accordance with Islamic teachings. Meanwhile, multicultural education is education in order to strive for and realize harmonization and the beauty of living together in diverse cultures, social backgrounds, languages, ethnicities, languages, groups and so on. The components of developing a multicultural Islamic Religious Education curriculum include objectives, content, methods/strategies, learning media and evaluation, all of which are interrelated. The material component for developing a multicultural Islamic religious education curriculum is equal rights (equity), tolerance (tolerance), humanity (humanity), precedes the dialog (prioritize dialogue) and justice (justice). Curriculum development at Islamic Boarding Schools for the Elderly can be carried out by adapting the abilities of the elderly who are oriented towards financial independence through the production of goods needed by the community using simple technology.